Periodization essentials and innovations in resistance training protocols - Brown, L. E.; Greenwood, M. (Strength and Conditioning Journal, 2005)
The following article deals with the important topic of periodization from a theory of fractal similarity. It attempts to establish a link between different cycles during a year-long training program, which may assist the reader in designing and writing a more comprehensive resistance prescription.